Travelers to unimaginable lands: stories of dementia, the caregiver, and the human brain - Kiper, Dasha (Random House, 2023)
"These compelling case histories meld science and storytelling to illuminate the complex relationship between the mind of someone with dementia and the mind of the person caring for them. After getting a master's degree in clinical psychology, Dasha Kiper became the live-in caregiver for a Holocaust survivor with Alzheimer's disease. For a year, she endured the emotional strain of looking after a person whose condition disrupts the rules of time, order, and continuity. Inspired by her own experience and her work counseling caregivers in the subsequent decade, Kiper offers an entirely new way to understand the symbiotic relationship between patients and those tending to them. Her book is the first to examine how the workings of the "healthy" brain prevent us from adapting to and truly understanding the cognitively impaired one. In these poignant but unsentimental stories of parents and children, husbands and wives, Kiper explores the existential dilemmas created by this disease: A man believes his wife is an impostor. A woman's imaginary friendships drive a wedge between herself and her devoted husband. Another woman's childhood trauma emerges to torment her son. A man's sudden Catholic piety provokes his wife. Why is taking care of a family member with dementia so difficult? Why do caregivers succumb to behaviors--arguing, blaming, insisting, taking symptoms personally--they know are counterproductive? Exploring the healthy brain's intuitions and proclivities, Travelers to Unimaginable Lands reveals the neurological obstacles to caregiving, enumerating not only the terrible pressures the disease exerts on our closest relationships but offering solace and perspective as well"--